1994
DOI: 10.1159/000147644
|View full text |Cite
|
Sign up to set email alerts
|

NO-Synthase-Containing Neurons of the Pig Inferior Mesenteric Ganglion, Part of Them Innervating the Ductus deferens

Abstract: The presence of nitric oxide-synthase (NOS) in neurons of the porcine inferior mesenteric ganglion (IMG) has been investigated. A minority (about 1-3%) of the neurons were immunoreactive (IR) for NOS, the vast majority of which stained for neuropeptide Y (NPY) but not for tyrosine hydroxylase (TH). A small subpopulation of prevertebral neurons, 1% of which stained for NOS or NADPH-diaphorase (NADPHd), projected to the ductus deferens, as demonstrated by retrograde tracing. Within the wall of the ductus deferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 0 publications
4
18
1
Order By: Relevance
“…Bilateral ganglia show tendency to fuse, forming the impaired structure in the pig and horse or 1-4 groups of neurons in the cat (Nickel et al 2004). The data regarding the pig are in contrast to our previous studies involving tracer investigations of genital organs and dealing with immunohistochemical properties of neurones innervating these organs (Kaleczyc et al 1994, Kaleczyc et al 1995, Kaleczyc 1998, Klimczuk and Kaleczyc 2010, Sienkiewicz 2010b. In these studies we always found the CaMG as the paired structure.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Bilateral ganglia show tendency to fuse, forming the impaired structure in the pig and horse or 1-4 groups of neurons in the cat (Nickel et al 2004). The data regarding the pig are in contrast to our previous studies involving tracer investigations of genital organs and dealing with immunohistochemical properties of neurones innervating these organs (Kaleczyc et al 1994, Kaleczyc et al 1995, Kaleczyc 1998, Klimczuk and Kaleczyc 2010, Sienkiewicz 2010b. In these studies we always found the CaMG as the paired structure.…”
Section: Discussioncontrasting
confidence: 78%
“…Immunohistochemical studies on CaMG were mainly performed in laboratory animas such as the rat (Herbrecht et al 1995, Sann et al 1995, guinea pig (McLachlan and Llewellyn-Smith 1986, Sann et al 1995, Parr andSharkey 1996) and cat (Cupo et al 1988, Bagnol et al 1993. Considering large animals, immunohistochemical properties of CaMG structures were investigated mainly in the pig, but except few papers , Lakomy et al 1996, Kaleczyc et al 2003 dealing with the general anatomy of this ganglion, most of the studies investigated specific subpopulations of CaMG neurones supplying different organs (Kaleczyc et al 1994, Kaleczyc et al 1995, Kaleczyc 1998, Pidsudko et al 2001, Klimczuk and Kaleczyc 2010, Sienkiewicz 2010a. However, the literature in the field contains no information on immunohistochemical features of the ovine CaMG.…”
Section: Introductionmentioning
confidence: 99%
“…With the possible exception of the testis, which is poorly supplied by mostly vasomotor nerve fibres, all male reproductive genitalia including accessory genital glands (AGG) receive an abundant innervation arising primarily from pelvic ganglia and, to a lesser extent, from inferior mesenteric ganglia, sympathetic chain ganglia as well as from dorsal root ganglia (DRG; Sjöstrand 1965;Costa and Furness 1973;Keast 1992;Kaleczyc et al 1993bKaleczyc et al , 1994Kaleczyc et al , 1995Kolbeck and Steers 1993;Mitchell 1994, Danuser et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Possibly the rate of discharge of the individual axon determines whether NO or noradrenaline is released in a manner similar to that which determines the release or otherwise of a colocalised neuropeptide (Lincoln and Burnstock, 1993). Interestingly, NO has also been implicated in the control of muscular tone in the wall of the pig vas deferens (Kaleczyc et al, 1994). The results of triplelabel immunohistochemical studies on the human neonatal and infant vas deferens (Jen et al, 1997) have shown that NOS coexists with NPY in many of the intramuscular noradrenergic nerves, indicating the possibility of corelease of NPY and NO with noradrenaline in such nerves.…”
Section: Nitric Oxidementioning
confidence: 99%